2021
DOI: 10.3748/wjg.v27.i6.487
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circVAPA promotes chemotherapy drug resistance in gastric cancer progression by regulating miR-125b-5p/STAT3 axis

Abstract: BACKGROUND Gastric cancer (GC) is a prevalent malignancy, leading to a high incidence of cancer-associated death. Cisplatin (DDP)-based chemotherapy is the principal therapy for clinical GC treatment, but DDP resistance is a severe clinical challenge and the mechanism remains poorly understood. Circular RNAs (circRNAs) have been identified to play crucial roles in modulating the chemoresistance of gastric cancer cells. AIM To explore the effect of circVAPA on chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Previous studies have revealed that miRNAs participate in the development of gastric cancer[ 16 , 17 ]. Meanwhile, a recent study has shown that miR-125b-5p is a tumor suppressor and involved in the modulation of gastric cancer[ 18 ]. In addition, signal transducer and activator of transcription (STAT)3 has been identified as an oncogene in gastric cancer[ 19 - 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that miRNAs participate in the development of gastric cancer[ 16 , 17 ]. Meanwhile, a recent study has shown that miR-125b-5p is a tumor suppressor and involved in the modulation of gastric cancer[ 18 ]. In addition, signal transducer and activator of transcription (STAT)3 has been identified as an oncogene in gastric cancer[ 19 - 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different from miR-199a-3p and miR-199a-5p, the role of miR-125b-5p in the pathogenesis of GC is not fully understood, but the identification results at the cell level and tissue level indicate that miR-125b-5p is significantly upregulated during the development of GC [ 39 ]. In addition, in a study on drug resistance, it was found that STAT3 may be a potential target of miR-125b-5p, and the signaling cascades involved in the regulation of chemotherapy drug resistance in GC [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…CircVAPA was expressed at high levels in GC tissues, and its downregulation enhanced the susceptibility of chemoresistant GC cells to DDP (Deng et al, 2021). CircVAPA upregulated STAT3 by interacting with miR-125b-5p.…”
Section: Cell Death Pathwaysmentioning
confidence: 97%
“…Thus, further functional and mechanistic studies are required to define the function of circ_0000338-miR-217/miR-485-3p feedback loops in CRC chemoresistance. Similarly, circ_0071589 expression was significantly elevated in DDP-resistant CRC tissues compared with sensitive tissues (Zhang W. et al, 2021). Circ_0071589 increased the expression of the oncogene kruppel-like factor 12 (KLF12) by interacting with miR-526b-3p.…”
Section: Cell Death Pathwaysmentioning
confidence: 99%